Mainstreaming Governance in Tajikistan through its Energy, Extractives, and Public Procurement Sectors - Mikulova, Kristina; Johns, Kimberly; Kunicova, Jana (World Bank, Washington, DC, 2014)
The governance partnership facility (GPF) supported program mainstreaming governance in Tajikistan portfolio (FY2010-14) was a landmark achievement in applying governance analysis and looking for entry points to improve transparency and accountability in key sectors in Tajikistan. This brief provides recommendations from its energy-efficiency audit, the extractive industries sector, and public procurement authority pilot program. In the long run, the government's goal is to use procurement performance measurement framework (PPMF) generated procurement performance assessments and annual procurement performance reports (APPRs) as feedback that inform policy design. If the reform momentum can be sustained, Tajikistan has a potential to gradually converge to good practices in public procurement and improve its good governance ratings over time.